TECHNOLOGIES OF CREATION AND A USAGE METHODS OF THE INTERACTIVE HELP IN DISTANCE LTARNING SYSTEM - Kravtsov, H.M.; Gnedkova, O.A.; Kozlovskij, E.O.; Ljakutin, V.V. (Journal of Information Technologies in Education (ITE), 2010)
Types and the structure of help modules of software of educational purpose are analyzed. The technological features of creation of interactive help systems are described. The features of the use of the interactive educational-help modules are considered in the distance learning system «Kherson Virtual University».